Rapid Progression of ALS with Low Back Pain Onset after Lumbar Decompressive Surgery : A Case Report - Suzuki, Youji; Uesaka, Toshio; Hanakita, Junya; Kuraishi, Keita; Takahashi, Toshiyuki; Watanabe, Mizuki; Murata, Daiki; Fukui, Nobuyuki; Kitahama, Yoshihiro (Japanese Journal of Neurosurgery, 2012)
Amyotrophic lateral sclerosis (ALS) is a fatal neurologic disease caused by progressive degeneration of the upper and lower motor neurons. An effective treatment for ALS has not been established, the average survival period is from two to three years.   Early symptoms of ALS are diverse and according to previous reports, 26.6% of patients are initially misdiagnosed, and approximately 10% of patients undergo inappropriate spinal surgery.   We report a case with progression of symptoms after lumbar spine surgery. The patient was a 68-year-old man. He was admitted complaining of low back pain with difficulty walking. The patient showed abnormal sensation in the lower extremities, and slight weakness of the left biceps femoris muscle, but muscle atrophy was not evident. Magnetic resonance imaging (MRI) showed lumbar spinal canal stenosis and a disc herniation of L4/5, so we performed decompressive surgery for this lesion. Despite complete decompression, the patient's symptoms did not improve. In addition, new problems developed in the early postoperative period including respiratory failure and lower extremity muscle atrophy. Following further examination, the patient was eventually diagnosed with ALS and died in the course of 4 months after surgery.   In this report, we discuss the symptoms associated with ALS with lower back pain. And we also consider the impact of surgery and anesthesia on the natural course of ALS.